The Impact of Foreign Direct Investment, Inflation, and Interest Rates on Economic Growth in Indonesia - Whinarko Juliprijanto; Maulia Siti Mukharohmah; Fauziah Eka Permadani; Nurul Fadhilah; Retno Rekayati (Jurnal REP (Riset Ekonomi Pembangunan), 2026)
This research examines the role of foreign direct investment (FDI), inflation, and interest rates in explaining economic growth in Indonesia over the period 1990–2024. The study employs the Autoregressive Distributed Lag (ARDL) approach to analyse both the existence of a long-run relationship and short-run dynamics among the variables. The ARDL bounds test finds no evidence of a long-run cointegrating relationship between economic growth, FDI, inflation, and interest rates. The short-run estimation indicates that economic growth is persistent over time, while the contemporaneous effects of interest rates and inflation are negative and statistically significant. However, their positive lagged effects largely offset the initial impacts, and the cumulative short-run effects are not statistically different from zero based on Wald tests. In contrast, FDI exhibits a positive but statistically insignificant coefficient, suggesting that no measurable short-run contribution of FDI to economic growth is identified in this study. These findings indicate that the estimated relationships primarily reflect temporary short-run adjustments rather than a stable long-run equilibrium and highlight the need for further research incorporating additional structural determinants of economic growth.